The protective role of Nrf2-Gadd45b against antimony-induced oxidative stress and apoptosis in HEK293 cells. (10th August 2016) - Jiang, Xingkang; An, Zesheng; Lu, Chao; Chen, Yue; Du, E; Qi, Shiyong; Yang, Kuo; Zhang, Zhihong; Xu, Yong
Highlights: Sb2 O3 -induces apoptosis in a ROS-dependent manner in HEK293 cells. Nrf2 protects HEK293 cells against Sb2 O3 -induced apoptosis. Gadd45b drives activation of MAPKs upon Sb2 O3 exposure. Nrf2 transcriptionally actives Gadd45b expression against Sb2 O3 -induced apoptosis. Abstract: Antimony (Sb) is one of the most prevalent heavy metals and frequently causes biological toxicity. However, the specific mechanisms by which Sb elicits its toxic effects remains to be fully elucidated. In this study, we found antimony trioxide (Sb2 O3 ) caused a dose-dependent cytotoxicity against HEK293 cells, and Sb2 O3 -induced excessive reactive oxygen species (ROS) was closely correlated with increased cell apoptosis. Mechanistic investigation manifested that nuclear factor NF-E2-related factor 2 (Nrf2) expression and nuclear translocation were significantly induced under Sb2 O3 treatment in HEK293 cells, and Nrf2 knockdown aggregated Sb2 O3 -induced cell apoptosis. Moreover, elevated Gadd45b expression actives the phosphorylation of MAPKs upon Sb2 O3 exposure, whereas Gadd45b knockdown diminished Sb2 O3 -induced activation of MAPKs and promoted cell apoptosis. In the meantime, however, the antioxidant N-acetylcysteine (NAC) was found to ameliorate Nrf2 expression and nuclear translocation as well as Gadd45b expression and MAPKs activation by repressing Sb2 O3 -induced ROS production. More importantly, we found Gadd45b was transcriptionally enhanced by Nrf2 through binding to three canonical antioxidant response elements (AREs) within its promoter region. Either Sb2 O3 or TBHQ (a selective Nrf2 activator) treatment, Gadd45b expression was significantly increased by luciferase assay. Nrf2 inhibition greatly diminished Gadd45b expression due to reduced binding of Nrf2 in Gadd45b promoter under Sb2 O3 treatment. To summarize, this study demonstrated the Nrf2-Gadd45b signaling axis exhibited a protective role in Sb-induced cell apoptosis.